Investigation of factors associated with symptom severity in patients with sinonasal polyposis - Aleksandra Aleksić; Zorica Novaković; Nataša Guzina-Golac; Vojin Vojnović; Željko Markić; Siniša Šolaja (Биомедицинска истраживања, 2019)
Introduction: Chronic rhinosinusitis with sinonasal polyposis is a chronic inflammatory process of the mucous membranes of the nasal and paranasal sinuses, clinically manifested by the appearance of polyps in the nasal cavity. The presence of polyps in the nose and sinuses is the cause of the characteristic symptoms that affect the quality of life of the patient. The study investigates the correlation between endoscopic, microbiological and radiological findings and symptom severity in patients with chronic rhinosinusitis and sinonasal polyposis. Methods: The research included 45 patients with chronic rhinosinusitis and sinonasal polyps, for whom surgery treatment was indicated after the failure of conservative therapy, and 25 healthy subjects. Intensity of symptoms in subjects was assessed by A Visual Analogue Scale. The bacteriological examination of secretion of the medial nasal corridor was carried out. Clinical and radiological assessment of the severity of the condition was done by the endoscopy and computerized tomography score (CT score). Results: A statistically significant difference was found in symptom severity between the experimental and control groups. There was a statistically significant correlation between endoscopy score and the symptom severity (r = 0.315; p = 0.035), CT-score (r = 0.720; p < 0.001) and the presence of asthma (r = 0.335; p = 0.025). Furthermore, there was a statistically significant correlation between CT score and the presence of asthma (r = 0.419; p =0.004). By binary logistic regression, a statistically significant correlation between the endoscopy score and symptom severity (OR = 1.513; p = 0.044) was found. Conclusion: In comparison with the objective clinical parameters, the severity of symptoms in patients with sinonasal polyposis is in a statistically significant correlation with the endoscopy score.
Keywords: chronic rhinosinusitis; sinonasal polyposis; VAS score; endoscopy score; computerized tomography score